Seeing the world through children's eyes : visual methodologies and approaches to research in the early years - White, E. Jayne (Visual pedagogies, methodologies & educational research, 2020)
"Seeing the World through Children's Eyes brings an overarching emphasis on 'seeing' to early years research. The book provides an opportunity to see and hear from leading researchers in the field concerning how they work with visual methodologies and young children. It explores the problems, pitfalls and promises that these offer for reflexive, critical inquiry that privileges the 'work of the eye' whilst implicating the researcher 'I' for what is revealed. Readers are invited to see for themselves what might be revealed through their discoveries, and to contemplate how these ideas might influence their own seeings"--